AaABF3, an Abscisic Acid–Responsive Transcription Factor, Positively Regulates Artemisinin Biosynthesis in Artemisia annua - Zhong, Yijun; Li, Ling; Hao, Xiaolong; Fu, Xueqing; Ma, Yanan; Xie, Lihui; Shen, Qian; Kayani, Sadaf; Pan, Qifang; Sun, Xiaofen; Tang, Kexuan (Frontiers in Plant Science, 2018)
Artemisinin is well known for its irreplaceable curative effect on the devastating parasitic disease, Malaria. This sesquiterpenoid is specifically produced in Chinese traditional herbal plant Artemisia annua. Earlier studies show that phytohormone abscisic acid (ABA) plays an important role in improving the artemisinin content, but how ABA regulates artemisinin biosynthesis is still poorly understood. In this study, we identified AaABF3 encoding an ABRE (ABA-responsive elements) binding factors. QRT-PCR analysis showed that AaABF3 expressed much higher in trichomes where artemisinin synthesizes and accumulates, and induced by ABA. To further investigate the mechanism through which AaABF3 regulates artemisinin biosynthesis, we carried out dual-luciferase analysis and yeast one-hybrid assay, and the results revealed that AaABF3 could directly bind to the promoter of ALDH1 gene, which is a key regulator in artemisinin biosynthesis, and activate the expression of ALDH1. Function analysis revealed that overexpression of AaABF3 in A. annua enhanced the production of artemisinin, while RNA interference of AaABF3 resulted in decreased artemisinin content. Taken together, our results demonstrate that AaABF3 plays an important role in ABA-regulated artemisinin biosynthesis through direct regulation of artemisinin biosynthesis gene, ALDH1.